Shattered dreams and hopeful hearts life stories of female child prostitutes. - Beato, Jin Krisve An A.; Con-ui, Rhea April A.; Pore, Maria Rechelyn D. (Tacloban City Jin Krisve An A. Beato, 2012)
This is a study on the different life stories of nine (9) female child prostitutes in Tacloban City. The participants were young individuals aged 18 and below who are currently involved in prostitution. The researchers conducted a semi-structured interview to gather relevant data. Results show that family background and peer pressure are major contributing factors which influence the participants' entry to prostitution, while the desire to earn money is what keeps them in their line of work. The participant's past and present experiences were also explored, including their feelings about their current situation, relationships with significant others, self-concept, and future plans in order to better understand the phenomenon of prostitution in the context of the child.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban
Keywords: Social Science